Modeling and experimental approaches for elucidating multi-scale uterine smooth muscle electro- and mechano-physiology: A review - Garrett, Amy S.; Means, Shawn A.; Roesler, Mathias W.; Miller, Kiara J. W.; Cheng, Leo K.; Clark, Alys R. (Frontiers in Physiology, 2022)
The uterus provides protection and nourishment (via its blood supply) to a developing fetus, and by contracting to deliver the baby at an appropriate time, thereby having a critical contribution to the life of every human. However, despite this vital role, it is an under-investigated organ, and gaps remain in our understanding of how contractions are initiated or coordinated. The uterus is a smooth muscle organ that undergoes variations in its contractile function in response to hormonal fluctuations, the extreme instance of this being during pregnancy and labor. Researchers typically employ various approaches to studying this organ, such as experiments on uterine muscle cells, tissue samples, or the intact organ, or the employment of mathematical models to simulate the electrical, mechanical and ionic activity. The complexity exhibited in the coordinated contractions of the uterus remains a challenge to understand, requiring coordinated solutions from different research fields. This review investigates differences in the underlying physiology between human and common animal models utilized in experiments, and the experimental interventions and computational models used to assess uterine function. We look to a future of hybrid experimental interventions and modeling techniques that could be employed to improve the understanding of the mechanisms enabling the healthy function of the uterus.